PENGARUH MEDIA BIG BOOK TERHADAP KEMAMPUAN BERBICARA ANAK USIA 5-6 TAHUN DI TK HIJRIAH III PALEMBANG - Tri Destika Wati; Tutut Tutut; Lidia Lidia (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2022)
This research is entitled "The influence of big book media on the speaking ability of children aged 5-6 years at Kindergarten Hijriah III Palembang". This type of research is a quantitative Experimental Design One Group Pre-test Post-test (one class). The research sample used in this study was group B1 in Tk Hijriah III Palembang, totaling 10 children, namely 5 boys and 5 girls. The sampling technique was carried out using Simple Random Sampling or the children were called one by one to the front of the class to retell the story. The data collection method uses observation tests and documentation with data analysis using normality tests and homogeneity tests. The results of the study and discussion of the average pre-test score that did not use treatment was 51, while the typical post-test score utilizing the big book or treatment media was 79. There was an effect when not using the media and after using the big book media. The results obtained by testing the hypothesis using the T-test obtained 16.667 with a significant level of 5% so that it can be 2,262. Because = 16,667 > = 2,262. So the conclusion is that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, meaning that there is an influence of the media on the speaking ability of children at Hijriah III Kindergarten in Palembang.